2017
DOI: 10.3389/fneur.2017.00119
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Outcome of European Tick-borne Encephalitis after Vaccine Failure

Abstract: Tick-borne encephalitis is a viral disease affecting the central nervous system. It is endemic in Switzerland with 200–250 notified cases annually. Active immunization is effective for persons in all age groups. Vaccine failure is rare, in particular after a completed vaccination course. Here, we describe the case of 67-year-old man with a fatal outcome despite vaccination. The diagnosis was confirmed by extensive postmortem analyses. The diagnostic challenges of vaccine failure in tick-borne encephalitis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 20 publications
2
13
2
2
Order By: Relevance
“…Thus, autoimmune conditions as a cause of LETM and viruses leading to anterior horn tractopathy including WNV and Herpes viruses needed to be excluded [16,17]. A similar observation to our CSF findings was made by the Swiss case where massive intrathecal IgM (92%) and IgG (73%) production was present [12]. In that patient, the combination of a history of a completed course of vaccination, the early serology results consistent with the vaccination and the rare incidence of vaccine failures markedly delayed the diagnosis.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Thus, autoimmune conditions as a cause of LETM and viruses leading to anterior horn tractopathy including WNV and Herpes viruses needed to be excluded [16,17]. A similar observation to our CSF findings was made by the Swiss case where massive intrathecal IgM (92%) and IgG (73%) production was present [12]. In that patient, the combination of a history of a completed course of vaccination, the early serology results consistent with the vaccination and the rare incidence of vaccine failures markedly delayed the diagnosis.…”
Section: Discussionsupporting
confidence: 87%
“…Of note, the presumed protection suggested by the history of complete active vaccination should not detain from diagnostic work-up. A similar observation is mentioned in a report of a fatal TBE breakthrough case with myeloradiculitis from Switzerland [12]. The neuropathological analysis revealed a predominantly T-cell-driven parenchymal infiltration, which implicates that the vaccine-induced T-cell and antibody response failed and subsequently allowed the virus to invade the brain parenchyma and the spinal cord.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The authors of previous studies have found that after a onebooster dose circulating antibodies persisted in 96-99% subjects (1,9,18). These data cannot be compared to our results, because we only analyzed the presence of antibodies after 2 and 3 doses of primary vaccination.…”
Section: Discussioncontrasting
confidence: 62%
“…Taip pat li te ra tû ro je ap ra ðo mi nuo EE vak ci nuo tø as me nø mir ties at ve jai [43]. Vy res ni pa cien tai tu ri reikð min gai maþes ná an ti kû nø kie ká [44], jiems bû din gas ma þes nis imu ninis at sa kas á vak ci nà [45].…”
Section: Vakcinacijaunclassified